2016
DOI: 10.1038/ncomms13710
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LOXL2 for cardiac interstitial fibrosis and heart failure treatment

Abstract: Interstitial fibrosis plays a key role in the development and progression of heart failure. Here, we show that an enzyme that crosslinks collagen—Lysyl oxidase-like 2 (Loxl2)—is essential for interstitial fibrosis and mechanical dysfunction of pathologically stressed hearts. In mice, cardiac stress activates fibroblasts to express and secrete Loxl2 into the interstitium, triggering fibrosis, systolic and diastolic dysfunction of stressed hearts. Antibody-mediated inhibition or genetic disruption of Loxl2 great… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
172
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(200 citation statements)
references
References 45 publications
12
172
0
2
Order By: Relevance
“…8E). As reported for transaortic constriction-induced CH [34], AngII also upregulated the other Lox family members (Loxl1, Loxl2, Loxl3, and Loxl4) in the heart (Fig. 9).…”
Section: Cardiac Cn Mediates Angii-induced Fibrosis and Profibrotic Gsupporting
confidence: 78%
See 1 more Smart Citation
“…8E). As reported for transaortic constriction-induced CH [34], AngII also upregulated the other Lox family members (Loxl1, Loxl2, Loxl3, and Loxl4) in the heart (Fig. 9).…”
Section: Cardiac Cn Mediates Angii-induced Fibrosis and Profibrotic Gsupporting
confidence: 78%
“…In recent years, new factors have been identified and characterized that trigger and maintain the myocardial fibrotic response in different cardiac diseases . An important role in pathological cardiac fibrosis was recently described for the lysyl oxidase (Lox) family of enzymes, which catalyze collagen assembly . Here, we show that suppression of cardiac Cn impairs the transcriptional expression of Lox , which is involved in the progression of a pathological fibrotic response in the heart.…”
Section: Discussionmentioning
confidence: 73%
“…AB0023 has been tested in cell lines and mice models before the humanized version entered clinical testing. AB0023 has been studied in the context of LOXL2 involvement in interstitial fibrosis and heart failure in mice dosed at 30 mg kg −1 twice a week . The transaortic constriction dysfunction was less seen in the treated mice and the transaortic constriction stressed heart also stabilized left ventricular fractional shortening .…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 99%
“…AB0023 has been studied in the context of LOXL2 involvement in interstitial fibrosis and heart failure in mice dosed at 30 mg kg −1 twice a week . The transaortic constriction dysfunction was less seen in the treated mice and the transaortic constriction stressed heart also stabilized left ventricular fractional shortening . It was concluded that LOXL2 has an effect on interstitial fibrosis and the dysfunction of the heart as they are involved in the activation of myofibroblasts, promoting the production of collagen within cardiac tissue …”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 99%
“…Likewise, targeting LOXL2 delivered promising results in other diseases such as reduction in stress-induced cardiac fibrosis 9. However, less enthusiastic results were obtained in idiopathic pulmonary fibrosis using a monoclonal antibody 10…”
mentioning
confidence: 99%